PROMOTION OF UNHEALTHY FOOD AND ITS INFLUENCE ON ANTISOCIAL BEHAVIOR - Bjelajac, Željko; Stošić, Lazar; Filipović, Aleksandar (Economics of Agriculture, 2023)
The goal of this paper is to explore the issue of promoting unhealthy food and its potential impact on antisocial behavior in contemporary society using methods of structural and functional analysis, quantitative and qualitative analysis, comparative analysis, descriptive methods, and survey methods. Unhealthy food with high-calorie, harmful nutritional ingredients, can cause a myriad of health issues, such as obesity, cardiovascular conditions, and diabetes, but in some instances, it can affect the behavior of individuals. The paper investigates how such promotion can affect individuals’ eating patterns and health, with a particular focus on the development of antisocial behaviors. It also considers risk factors, including socioeconomic aspects and the influence of the media, that support the promotion of unhealthy food. This paper also discusses potential strategies to reduce the promotion of unhealthy food and promote healthier choices to mitigate the negative effects on antisocial behavior and enhance societal well-being.